2015
DOI: 10.1007/s00296-015-3355-5
|View full text |Cite
|
Sign up to set email alerts
|

Increase in thyroid stimulating hormone levels in patients with gout treated with inhibitors of xanthine oxidoreductase

Abstract: Increase in thyroid stimulating hormone (TSH) levels over the upper normal limit has been reported in a small percentage of patients treated with febuxostat in clinical trials, but a mechanistic explanation is not yet available. In an observational parallel longitudinal cohort study, we evaluated changes in TSH levels in patients with gout at baseline and during urate-lowering treatment with febuxostat. Patients to be started on allopurinol who had a measurement of TSH in the 6-month period prior to baseline e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…However, the majority of previous studies are consistent with our ndings. A previous large-scale cross-sectional study documented a linear association between FT4 and SUA in general subjects [12]. The risk of hyperuricemia was also signi cantly increased in individuals with higher FT4 level [12].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the majority of previous studies are consistent with our ndings. A previous large-scale cross-sectional study documented a linear association between FT4 and SUA in general subjects [12]. The risk of hyperuricemia was also signi cantly increased in individuals with higher FT4 level [12].…”
Section: Discussionmentioning
confidence: 86%
“…A previous large-scale cross-sectional study documented a linear association between FT4 and SUA in general subjects [12]. The risk of hyperuricemia was also signi cantly increased in individuals with higher FT4 level [12]. Additionally, a recent study also demonstrated that the decrease of SUA by the treatment of febuxostat or allopurinol exerted effects on the elevation of TSH in patients with gout [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, several observational studies reported abnormally increased level of serum uric acid among patients with hypothyroidism or hyperthyroidism, suggesting that uric acid may be involved in development or progression of thyroid dysfunction [45][46][47]. Finally, urate-lowering drugs used in patients with gout or hyperuricemia proved to increase TSH level in a dose-dependent way, providing another explanation for the increased risk of hypothyroidism among patients with gout or hyperuricemia [48]. However, the molecular mechanisms underlying the increased risk of thyroid disorders among gout and hyperuricemic patients are still elusive, and need to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…При длительном применении фебуксостата у 5,5% пациентов отмечалось повышение концентрации тирео-тропного гормона (>5,5 мкМЕ/мл), в связи с чем пациен-там с нарушением функции щитовидной железы фебук-состат следует назначать с осторожностью [67].…”
Section: безопасностьunclassified